INTERNAL CONTROL SYSTEM PROBLEMS, CHALLENGES AND ISSUES OF ITS IMPROVEMENT (Globalization and Business, 2023)
The activities of the budget institution are directly related to the society and each successful step is aimed at the development of the country. An effective system of internal control is the main lever for managing and minimizing the risks in budgetary institutions. That is why the study and elimination of problems and shortcomings related to internal control will functionally strengthen this system, which will have a positive impact on the efficiency of the functioning of budgetary institutions. The results of the research work and the recommendations developed based on it, will help budget institutions to improve the internal control system and, consequently, to manage risks.  Resources in the public sector are created based on public money and therefore should be used in the public interest. That is why it is very important in the public sector to control the acquisition, use and protect the existing resources, which is regulated by the internal control system.  The article deals with the issues of an effective internal control system and its quality assurance in Georgia. The paper discusses the importance of the internal control system and its components, the role, and importance of quality assurance of the internal control system about the identified problematic issues. The role and benefits of internal audit as an integral part of the internal control system are evaluated and analyzed on the example of the Georgian budget institution.  Based on the conducted research and analysis, relevant conclusions have been made and problematic issues related to the internal control systems in the budget sector of Georgia have been assessed.